Study on Steroid Utilization Pattern in a Tertiary Care Teaching Hospital - Aryal, Arjan; Kunwar, Keshav; Shadvar, Sepideh; Kharel, Sanju; Ramasamy, Rajeswari; Shashidhar, Gopalakrishna; Aneesh, Samayam; Nazeem, Teena (Indian Journal of Pharmacy Practice)
Background: Rational use of corticosteroids is very essential for improving patient safety on long term use. AIM: To study the prescribing pattern of steroids in teaching hospital. Method: A prospective observational study was conducted in the department of dermatology and general medicine in a tertiary care teaching hospital for the period of 6 months. All patients receiving any category of Steroid therapy were included and the prescribing and tapering pattern of steroids were reviewed. Result: Prescribing pattern was observed and analysed in 226 participants during the study period. Steroids were prescribed for various Respiratory illnesses (59.32 %) and Skin related conditions (33.18%). The steroid utilization was found to be more in elderly patients, particularly males. Inhaler administration was common in 44.5% of cases. Budesonide was the most commonly prescribed (43.45%) followed by Prednisolone (15.25%) and Hydrocortisone (14.91%). Budesonide + Hydrocortisone were the most common therapy given in combination (35.19%). In topical preparation, Ultra potent Steroid Clobetasol (45.93%) was commonly prescribed and in Systemic Preparation, Intermediate acting steroid Prednisolone (37.82%) was used. Most drugs were prescribed rationally although some factors like improper history, drug administration time and tapering were deviating away from rationality. Conclusion: Not much variation was found in the pattern of prescription amongst the healthcare professionals. Although most of the drugs were prescribed rationally, involvement of a Clinical pharmacist in patient care can help in more rational prescribing along with prevention and early detection of ADRs which can directly promote drug safety and better patient outcomes.
Keywords: Prescribing pattern; Rationality; Tapering; Steroids; General Medicine; Dermatology